Heterogeneous element doped carbon coated polyanion positive electrode material and preparation method thereof

By forming a carbon coating layer of phosphorus and nitrogen in the core material of the cosmetic battery positive material, the problem of insufficient capacity and cycle performance of the existing positive pole materials and the stability of the structure of the existing positive pole material and the stability of the structure of the existing positive pole material sex.

CN119361638AActive Publication Date: 2025-01-24HUNAN MEITE XINCAILIAO SCI & TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411473496.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The capacity and circulation performance of existing sodium ion battery cathode materials are insufficient, making it difficult to meet the needs of large-scale energy storage and small power fields.

Method used

Polyclac ion positive material covered with miscellaneous elements doped carbon covering, its structure is NA3+XM2+X (PO4) 1+XP2O7@p-n/C. By forming a carbon bag mixed with phosphorus and nitrogen elements on the surface of the core material, it forms a carbon bag. Overwriting, improve the electrical and activity of materials.

Benefits of technology

It significantly improves the capacity and cycle performance of the cathode material, enhances the overall performance of the material, including conductivity and structural stability, while avoiding the adverse effects of phosphorus element doping on the phase composition of the core material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361638A_ABST
    Figure CN119361638A_ABST
Patent Text Reader

Abstract

The invention provides a heteroelement-doped carbon-coated polyanion positive electrode material, the structural general formula is Na < 3 + x > M < 2 + x > (PO4) < 1 + x > P2O7 (at) P-N / C, 0 < = x < = 2, M is one or more of Ni, Fe, Co and Mn, the polyanion positive electrode material is of a core-shell structure, Na < 3 + x > M < 2 + x > (PO4) < 1 + x > P2O7 is the core of the core-shell structure of the polyanion positive electrode material, (at) P-N / C represents a coating layer formed on the surface of the core material, and (at) P-N / C represents a coating layer formed on the surface of the core material. And P-N / C is a carbon coating layer co-doped with a phosphorus element and a nitrogen element. The heteroelement-doped carbon-coated polyanion positive electrode material is of a core-shell structure, the phosphorus element and nitrogen element co-doped carbon coating layer on the surface of the Na < 3 + x > M < 2 + x > (PO4) < 1 + x > P2O7 material is of a sheet structure, has a higher sp2 hybrid carbon structure and is excellent in conductivity, and the phosphorus element and nitrogen element co-doped carbon coating layers are mutually matched to reasonably activate a heterophase, so that the conductivity of the positive electrode material is improved. The high-conductivity P-N / C, the phosphorus element and the nitrogen element co-doped carbon coating layer and the core Na < 3 + x > M < 2 + x > (PO4) < 1 + x > P2O7 generate a synergistic effect, so that the overall performance, including the capacity and the cycle performance, of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery positive electrode materials, and in particular to a heteroelement-doped carbon-coated polyanion positive electrode material and a preparation method thereof. Background Art

[0002] In recent years, due to the limitation of lithium resources and high cost, sodium-ion batteries (SIBs) have attracted the attention of countries around the world in the field of large-scale energy storage and small power due to the advantages of relatively high natural abundance of sodium resources, potential low raw material costs and good electrochemical performance, and have gradually become an important optional technology route in the "post-lithium battery era". Since the hard carbon negative electrode can provide a reversible capacity of about 300mAh / g in the SIBs system, the primary challenge for the practical application of SIBs is the lack of low-cost and high-performance positive electrode materials.

[0003] In the early stage of the research, inspired by the successful experience of LiFePO4 in lithium-ion batteries, NaFePO4 became the focus of research due to its high specific capacity of 155mAh / g. Unfortunately, unlike LiFePO4, thermodynamically stable maricite-NaFePO4 is electrochemically inert, while electrochemically active olivine-NaFePO4 is not a thermodynamically stable phase structure, and the preparation process is very complicated (Vacuum, 2023, 210: 111853). In addition, Na2FeP2O7 derived from NaFePO4 can be directly synthesized through a solid-state route, and its lattice distortion is small during the charge and discharge process, so it has good cycle performance and strong structural stability. However, this cathode material is limited by its single-electron reaction, resulting in a low theoretical capacity (about 97.1mAh / g), which greatly hinders its commercial application. The iron-based composite phosphate (NFPP) that combines the advantages of both NaFePO4 and Na2FeP2O7 can produce a theoretical specific capacity of about 128.9 mAh / g. Coupled with its low volumetric strain, high thermal stability and higher working potential, it is considered to be a promising SIBs positive electrode material with a NASICON structure.

[0004] In recent years, a large number of studies on NFPP have been published. For example, the team of Professor Xia Yongyao of Fudan University reported a Na3Fe2PO4P2O7 cathode material composed of NaFePO4 and Na2FeP2O7 in a 1:1 molar ratio, and added r-GO to increase the conductivity of the material, but its actual specific capacity is not high, with a specific capacity of 110.2mAh / g at 0.1C (ACS Energy Lett. 2020, 5, 3788-3796). The team of Professor Cao Yuliang of Wuhan University further increased the molar ratio of NaFePO4 and Na2FeP2O7 to 2:1, and the specific capacity of the prepared material was improved to 110.9mAh / g at 0.2C (Nano Energy 91 (2022) 106680). Increasing the proportion of NaFePO4 in the composite phosphate will increase the theoretical specific capacity of the material, but in most of the current NFPP research work, simply changing the proportion of NaFePO4 in the composite phosphate is not enough to improve the battery performance of the iron-based composite phosphate (NFPP) cathode material. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a heteroelement-doped carbon-coated polyanion positive electrode material and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a polyanion positive electrode material doped with heteroelement carbon, the structural formula of the polyanion positive electrode material is

[0007] Na 3+x M 2+x (PO4) 1+x P2O7@PN / C, wherein 0≤x≤2, M is one or more of Ni, Fe, Co, and Mn, and the polyanion cathode material is a core-shell structure, Na 3+x M 2+x (PO4) 1+x P2O7 is the core of the core-shell structure of the polyanion positive electrode material, @PN / C represents a coating layer formed on the surface of the core material, and PN / C is a carbon coating layer co-doped with phosphorus and nitrogen.

[0008] The above-mentioned heteroelement-doped carbon-coated polyanion cathode material is a core-shell structure. 3+x M 2+x (PO4) 1+ x The surface of P2O7 material forms a PN / C coating layer, a carbon coating layer co-doped with phosphorus and nitrogen, which is a flaky structure and has a high sp 2Hybrid carbon structure, excellent conductivity, and phosphorus and nitrogen co-doped carbon coating layer cooperate with each other, reasonably activate the hybrid phase, improve capacity and cycle performance, high conductivity PN / C, phosphorus and nitrogen co-doped carbon coating layer, and core Na 3+x M 2+x (PO4) 1+x The synergistic effect of P2O7 improves the overall performance of the material, including capacity and cycle performance. Moreover, the doping of phosphorus is different from that of other elements in the coating layer. 3+x M 2+x (PO4) 1+x The P2O7 material is mainly composed of phosphate pyrophosphate, and phosphorus is doped into the coating layer. 3+x M 2+x (PO4) 1+x The phase composition of P2O7 does not cause adverse interference, and the high conductivity PN / C is achieved. The carbon coating layer co-doped with phosphorus and nitrogen is 3+ x M 2+x (PO4) 1+x P2O7 produces synergy and overcomes the adverse effects of phosphorus doping on the phase composition of the core material.

[0009] In heteroelement-doped carbon-coated polyanion cathode materials, Na 3+x M 2+x (PO4) 1+x The P2O7 material may be composed of a multiphase structure, specifically including one or more phases such as NaMPO4, Na2MP2O7 and Na4M3(PO4)2P2O7; wherein, when 0≤x<1, the positive electrode material is a mixed phase structure composed of Na2MP2O7 and Na4M3(PO4)2P2O7; when x=1, the positive electrode material is a pure phase structure of Na4M3(PO4)2P2O7; when 1<x≤2, the positive electrode material is a mixed phase structure composed of NaMPO4 and Na4M3(PO4)2P2O7. The phase of the material can be controlled by controlling the proportion of the source material during the preparation of the material.

[0010] Preferably, the preparation method of PN / C comprises dispersing an organic carbon source, an organic phosphorus source and an organic nitrogen source uniformly, heating to 600-1000° C. in an inert gas atmosphere, and then sintering at a constant temperature for 5-20 hours to obtain a PN / C carbon material.

[0011] The above-mentioned heteroelement-doped carbon-coated polyanion positive electrode material is prepared by sintering an organic carbon source, an organic phosphorus source, and an organic nitrogen source to prepare a phosphorus- and nitrogen-coated carbon material (PN / C), and then reacting with Na 3+x M2+x (PO4) 1+x The mixed sintering of the source materials of P2O7 material overcomes the adverse effect of phosphorus doping on the phase composition of the core material.

[0012] Preferably, M is one or more of Ni, Fe and Co.

[0013] Preferably, 1≤x≤2.

[0014] Preferably, the mass of the PN / C coating layer accounts for 0.1% to 5.0% of the mass of the polyanion positive electrode material.

[0015] Preferably, the mass of the PN / C coating layer accounts for 0.5% to 3.0% of the mass of the polyanion positive electrode material.

[0016] The above-mentioned heteroelement-doped carbon-coated polyanion positive electrode material has been studied and found that when the mass of the PN / C coating layer accounts for 0.5% to 3.0% of the mass of the polyanion positive electrode material, the heteroelement-doped carbon-coated polyanion positive electrode material has better capacity and cycle performance.

[0017] Preferably, in the process of preparing the PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic phosphorus source, organic nitrogen source and organic carbon source used is a:b:100, wherein 1.0≤a≤5.0; 20≤b≤50.

[0018] Preferably, in the process of preparing the PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic phosphorus source, organic nitrogen source and organic carbon source used is a:b:100, wherein 3≤a≤8; 30≤b≤45.

[0019] The study found that when the weight ratio of phosphorus, nitrogen and carbon in the organic phosphorus source, organic nitrogen source and organic carbon source meets the above requirements, the polyanion positive electrode material doped with carbon has better capacity and cycle performance.

[0020] Preferably, the organic carbon source is one or more of glucose, chitosan, sucrose, starch, citric acid, sodium citrate, lauric acid, and sodium laurate.

[0021] Preferably, the organic phosphorus source is one of triphenylphosphine and phytic acid.

[0022] Preferably, the organic nitrogen source is one or more of melamine, urea and chitosan.

[0023] Preferably, the preparation method of the polyanion positive electrode material comprises the steps of: sintering the PN / C carbon material and Na 3+x M 2+x (PO4) 1+xThe precursor materials of P2O7 are dispersed and mixed, and then heated to 420-600°C in an inert gas atmosphere and sintered at a constant temperature for 5-20 hours to obtain Na 3+x M 2+x (PO4) 1+x P2O7@PN / C.

[0024] Preferably, Na 3+x M 2+x (PO4) 1+x The source materials of P2O7 include sodium source, M source and phosphorus source.

[0025] Preferably, the sodium source is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrate, and sodium citrate.

[0026] More preferably, the sodium source is one or more of sodium dihydrogen phosphate, sodium phosphate, sodium pyrophosphate, sodium carbonate and sodium citrate.

[0027] Preferably, the M source is one or more of phosphates, nitrates, sulfates, oxalates, acetates and oxides corresponding to one or more elements of Ni, Fe, Co and Mn.

[0028] Preferably, the phosphorus source is one or more of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, sodium pyrophosphate, ferric phosphate, and ferric pyrophosphate.

[0029] More preferably, the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, and iron phosphate.

[0030] The present invention also provides a method for preparing any of the above-mentioned heteroelement-doped carbon-coated polyanion positive electrode materials, the method comprising the following steps:

[0031] (1) grinding and mixing an organic carbon source, an organic nitrogen source, and an organic phosphorus source according to a weight ratio, and then sintering in one step or two steps under an inert gas atmosphere to obtain a PN / C carbon material;

[0032] (2) according to the preset x value, the PN / C carbon material, the sodium source, the M source and the dispersant are dispersed or dissolved in a solvent according to a stoichiometric ratio and ground to obtain a mixed slurry H2, and after removing the solvent and drying H2, a precursor material to be sintered H3 in which each element is evenly dispersed is obtained;

[0033] (3) The obtained H3 is subjected to a one-step or two-step sintering treatment in an inert atmosphere to obtain a polyanion positive electrode material doped with an impurity element and coated with an element-doped carbon.

[0034] Preferably, in step (1), the grinding process is a ball milling process, wherein the rotation speed of the ball milling process is 400-800 rpm, the ball-to-material ratio is 2-20:1, the diameter of the zirconia ball is 0.1-0.5 mm, and the ball milling time is 2-5 h.

[0035] Preferably, in step (2), the grinding process includes a ball milling process and a sand milling process in sequence, wherein the ball milling speed is 400-800 rpm; the ball-to-material ratio is 2-20:1, and the diameter of the zirconia ball is 0.1-0.5 mm; the solid content of the sand milling is 15%-40%, and the sand milling speed is 1000-2400 rpm; the particle size of the solid in the slurry after sand milling is D50≤6μm, Dmax≤30μm.

[0036] Preferably, in step (2), the dispersant is one or more of PVP, PVA, NPEOs, PEG, APG, and PAA.

[0037] Preferably, in step (2), the solvent is one of water, methanol, ethanol, acetone, ethylene glycol and n-butanol.

[0038] Preferably, in step (2), the drying method is spray drying, freeze drying, high temperature drying or vacuum drying, and the drying temperature is not higher than 280°C.

[0039] More preferably, the drying method is spray drying; the inlet air temperature of the spray drying is 180-280°C, and the outlet air temperature is 80-120°C.

[0040] Preferably, in step (1), in the one-step sintering or the two-step sintering, the procedure of the one-step sintering is, in an inert protective atmosphere, heating to 600-1000°C at a heating rate of 1-5°C / min, and sintering at a constant temperature for 5-20 hours; then cooling to room temperature at a cooling rate of 2-10°C / min; the procedure of the two-step sintering is, in an inert protective atmosphere, heating to a pre-sintering temperature of 400-550°C at a heating rate of 1-5°C / min for 2-4 hours; then heating to 600-1000°C at a heating rate of 3-6°C / min for 4-10 hours; then cooling to room temperature at a cooling rate of 2-10°C / min.

[0041] Preferably, in step (3), in the one-step sintering or the two-step sintering, the procedure for the one-step sintering is, in an inert protective atmosphere, heating to 420-600°C at a heating rate of 1-5°C / min, and sintering at a constant temperature for 5-20 hours; then cooling to room temperature at a cooling rate of 2-10°C / min; the procedure for the two-step sintering is, in an inert protective atmosphere, heating to a pre-sintering temperature of 250-420°C at a heating rate of 1-5°C / min for 2-4 hours; then heating to 520-600°C at a heating rate of 3-6°C / min for 4-10 hours; then cooling to room temperature at a cooling rate of 2-10°C / min.

[0042] The beneficial effects of the present invention are as follows: the present invention provides a heteroelement-doped carbon-coated polyanion cathode material and a preparation method thereof. The heteroelement-doped carbon-coated polyanion cathode material of the present invention is a core-shell structure. 3+x M 2+x (PO4) 1+x The surface of P2O7 material, PN / C, phosphorus and nitrogen co-doped carbon coating, is a sheet structure with high sp 2 Hybrid carbon structure, excellent conductivity, and phosphorus and nitrogen co-doped carbon coating layer cooperate with each other, reasonably activate the hybrid phase, improve capacity and cycle performance, high conductivity PN / C, phosphorus and nitrogen co-doped carbon coating layer, and core Na 3+x M 2+x (PO4) 1+x The synergistic effect of P2O7 improves the overall performance of the material, including capacity and cycle performance. Moreover, the doping of phosphorus is different from that of other elements in the coating layer. 3+x M 2+x (PO4) 1+x P2O7 material is mainly composed of phosphate pyrophosphate, and phosphorus is doped as a coating layer. 3+x M 2+x (PO4) 1+x The phase composition of P2O7 does not cause adverse interference, and the high conductivity PN / C is achieved. The carbon coating layer co-doped with phosphorus and nitrogen is 3+x M 2+x (PO4) 1+x P2O7 produces synergy and overcomes the adverse effects of phosphorus doping on the phase composition of the core material. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The present invention is a schematic diagram of the preparation process of the heteroelement-doped carbon-coated polyanion positive electrode material.

[0044] Figure 2This is a scanning electron microscope image of the PN / C prepared in Example 1 of the heteroelement-doped carbon-coated polyanion positive electrode material of the present invention.

[0045] Figure 3 The Na prepared in Example 1 of the heteroelement-doped carbon-coated polyanion positive electrode material of the present invention 4.3 M 3.3 (PO4) 2.3 Scanning electron microscope image of P2O7@PN / C.

[0046] Figure 4 These are X-ray diffraction patterns of the heteroelement-doped carbon-coated polyanion positive electrode materials of Example 1, Example 14, and Example 15; Intensity in the figure represents intensity.

[0047] Figure 5 The charge and discharge curves of the sodium ion button cells assembled from the samples of Example 1 and Example 10 of the heteroelement-doped carbon-coated polyanion cathode material of the present invention at a rate of 0.1C, with an operating voltage of 1.5-4.0 V vs. Na + / Na; in the figure, Voltage represents voltage, and Specific capacity represents specific capacity.

[0048] Figure 6 The cycle curve diagram of the sodium ion button battery assembled with the samples of Example 1 and Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the heteroelement-doped carbon-coated polyanion positive electrode material of the present invention; in the figure, Specific capacity represents the specific capacity, and Cycle number represents the number of cycles. DETAILED DESCRIPTION

[0049] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0050] Example 1

[0051] As a heteroelement-doped carbon-coated polyanion positive electrode material according to an embodiment of the present invention, the general structural formula of the polyanion positive electrode material is Na 3+x M 2+x (PO4) 1+x P2O7@PN / C, wherein x=1.3, M is Fe, and the polyanion cathode material is a core-shell structure, Na 3+x M 2+x (PO4) 1+xP2O7 is the core of the core-shell structure of the polyanion positive electrode material, @PN / C represents the coating formed on the surface of the core material, and PN / C is a carbon coating layer co-doped with phosphorus and nitrogen. Thermogravimetric analysis method was used to determine that the mass of the PN / C coating layer accounted for 1.80% of the mass of the polyanion positive electrode material.

[0052] The different contents of phosphorus, nitrogen and carbon in the PN / C carbon material are controlled by adding different amounts of organic carbon source, organic nitrogen source and organic phosphorus source in the preparation method. Specifically, the weight ratio of phosphorus, nitrogen and carbon in the organic carbon source, organic nitrogen source and organic phosphorus source is 2:30:100;

[0053] The method for preparing the heteroelement-doped carbon-coated polyanion positive electrode material comprises the following steps:

[0054] (1) grinding and mixing an organic carbon source, an organic nitrogen source, and an organic phosphorus source according to a weight ratio, and then sintering in an inert gas atmosphere to obtain a PN / C carbon material; the organic carbon source is chitosan, the organic phosphorus source is triphenylphosphine, and the organic nitrogen source is urea; the grinding process used is a ball milling process, wherein the speed of the ball milling process is set to 600 rpm, the ball-to-material ratio is 10:1, the diameter of the zirconia ball is 0.2 mm, and the ball milling time is 2 h;

[0055] The one-step sintering procedure is to heat the sample to 900°C at a heating rate of 3°C / min in a nitrogen inert atmosphere, sinter at a constant temperature for 8 h, and then cool the sample to room temperature at a cooling rate of 5°C / min.

[0056] (2) Dispersing or dissolving PN / C carbon material, sodium source, M source and PVA dispersant in methanol solvent according to the stoichiometric ratio and grinding to obtain a mixed slurry H2, and drying H2 to obtain a precursor material H3 in which all elements are evenly dispersed; the drying method is spray drying, the inlet air temperature of the spray drying is 250°C, and the outlet air temperature is 110°C; the grinding process includes a ball milling process and a sand milling process in sequence, wherein the solid content of the ball milling and the ball milling is 25%; the ball milling speed is 600rmp; the ball-to-material ratio is 6:1, and the diameter of the zirconia ball is 0.3mm; the sand milling speed is 1500rmp; the particle size of the solid in the slurry after sand milling is D50≤6μm, Dmax≤30μm; the sodium source is sodium dihydrogen phosphate, the M source is Ni oxalate; the phosphorus source is ammonium dihydrogen phosphate;

[0057] (3) The obtained H3 is subjected to a one-step sintering treatment in a nitrogen inert atmosphere to obtain a polyanion positive electrode material doped with an impurity element and coated with an element-doped carbon; the one-step sintering procedure is as follows: in a nitrogen inert protective atmosphere, the temperature is increased to 520°C at a heating rate of 3°C / min, and the temperature is kept constant for 9 hours; and then the temperature is cooled to room temperature at a cooling rate of 5°C / min.

[0058] Example 2

[0059] As a heteroelement-doped carbon-coated polyanion positive electrode material of the present invention, the only difference between this embodiment and embodiment 1 is that: by controlling the preparation method step (2), the PN / C carbon material and Na 3+x M 2+x (PO4) 1+x The weight proportion of the P2O7 source material was determined by thermogravimetric analysis to be 0.21% of the weight of the PN / C coating layer.

[0060] Example 3

[0061] As a heteroelement-doped carbon-coated polyanion positive electrode material of the present invention, the only difference between this embodiment and embodiment 1 is that: by controlling the preparation method step (2), the PN / C carbon material and Na 3+x M 2+x (PO4) 1+x The weight proportion of the P2O7 source material was determined by thermogravimetric analysis to be 0.53% of the weight of the PN / C coating layer of the polyanion positive electrode material.

[0062] Example 4

[0063] As a heteroelement-doped carbon-coated polyanion positive electrode material of the present invention, the only difference between this embodiment and embodiment 1 is that: by controlling the preparation method step (2), the PN / C carbon material and Na 3+x M 2+x (PO4) 1+x The weight proportion of the P2O7 source material was determined by thermogravimetric analysis to be 1.18% of the weight of the PN / C coating layer of the polyanion positive electrode material.

[0064] Example 5

[0065] As a heteroelement-doped carbon-coated polyanion positive electrode material of the present invention, the only difference between this embodiment and embodiment 1 is that: by controlling the preparation method step (2), the PN / C carbon material and Na 3+x M 2+x (PO4) 1+xThe weight proportion of the P2O7 source material was determined by thermogravimetric analysis to be 3.27% of the weight of the PN / C coating layer of the polyanion positive electrode material.

[0066] Example 6

[0067] As a heteroelement-doped carbon-coated polyanion positive electrode material of the present invention, the only difference between this embodiment and embodiment 1 is that: by controlling the preparation method step (2), the PN / C carbon material and Na 3+x M 2+x (PO4) 1+x The weight proportion of the P2O7 source material was determined by thermogravimetric analysis to be 4.18% of the weight of the PN / C coating layer of the polyanion positive electrode material.

[0068] Example 7

[0069] As a heteroelement-doped carbon-coated polyanion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 1 is that when preparing the PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic carbon source, organic nitrogen source and organic phosphorus source is 4.5:30:100.

[0070] Example 8

[0071] As a heteroelement-doped carbon-coated polyanion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 1 is that when preparing the PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic carbon source, organic nitrogen source and organic phosphorus source is 7.5:40:100.

[0072] Example 9

[0073] As a heteroelement-doped carbon-coated polyanion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 1 is that when preparing the PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic carbon source, organic nitrogen source and organic phosphorus source is 10:35:100.

[0074] Example 10

[0075] As a heteroelement-doped carbon-coated polyanion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 1 is that when preparing the PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic carbon source, organic nitrogen source and organic phosphorus source is 5:20:100.

[0076] Embodiment 11

[0077] As a heteroelement-doped carbon-coated polyanion positive electrode material according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that M is Ni.

[0078] Example 12

[0079] As a heteroelement-doped carbon-coated polyanion positive electrode material according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that M is Mn.

[0080] Embodiment 13

[0081] As a heteroelement-doped carbon-coated polyanion positive electrode material according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that M is Co.

[0082] Embodiment 14

[0083] As a heteroelement-doped carbon-coated polyanion positive electrode material according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that x=0.6.

[0084] Embodiment 15

[0085] As a heteroelement-doped carbon-coated polyanion positive electrode material according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that x=1.

[0086] Comparative Example 1

[0087] As a comparative example of the present invention, a heteroelement-doped carbon-coated polyanion positive electrode material is used. The only difference between this comparative example and Example 1 is that the coating layer material is different, and the coating layer is prepared from an organic carbon source, and does not contain phosphorus and nitrogen doping. The specific operation is that in step (1) of the preparation method, except that the organic nitrogen source and the organic phosphorus source are not added, the rest of the grinding treatment and sintering treatment are exactly the same.

[0088] Comparative Example 2

[0089] As a heteroelement-doped carbon-coated polyanion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that the coating layer material is different, does not contain phosphorus, and the phosphorus content is supplemented by nitrogen.

[0090] Comparative Example 3

[0091] As a heteroelement-doped carbon-coated polyanion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that the coating layer material is different, does not contain nitrogen, and the nitrogen content is supplemented by phosphorus.

[0092] Experimental methods

[0093] 1. Material Characterization

[0094] The heteroelement-doped carbon-coated polyanion positive electrode materials of Example 1, Example 2, Example 3, Example 10, Example 14, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were characterized.

[0095] The PN / C and positive electrode samples prepared in Example 1 of the present invention were subjected to scanning electron microscopy, and the results are as follows: Figure 2 and Figure 3 shown.

[0096] In order to explore the different values ​​of x, the prepared Na 3+x M 2+x (PO4) 1+x The specific structure and composition of the P2O7 positive electrode material are shown in Figure 1. The samples of Example 14 and Example 15 were subjected to X-ray diffraction. Figure 4 As shown; Intensity in the figure represents intensity.

[0097] In order to explore the effect of carbon materials doped with different weight ratios of impurity elements on the performance of positive electrode materials, electrochemical performance tests were carried out on samples of Example 1 and Example 10. Figure 5 The charge and discharge curve of the sodium ion button battery assembled from the above samples at a rate of 0.1C, with an operating voltage of 1.5~4.0V vs.Na + / Na; in the figure, Voltage represents voltage, and Specificcapacity represents specific capacity.

[0098] In order to explore the effect of impurity doping on the performance of the positive electrode material, the samples of Example 1 and Comparative Examples 1-3 were subjected to a charge-discharge cycle performance test at 1C, and the voltage range of the constant current charge-discharge test was 1.5-4.0V; Figure 6 It is a cycle curve diagram of Example 1 and Comparative Examples 1, 2 and 3; in the figure, Specific capacity represents specific capacity, and Cyclenumber represents the number of cycles.

[0099] 2. Battery performance test

[0100] Battery performance test method: The mixed phosphate material prepared in Examples 1 to 15 and Comparative Examples 1 to 4 is used as the positive electrode material of the sodium ion battery. In a drying room (humidity below 15%), the positive electrode active material, the conductive agent (super-P) and the binder (PVDF) are added to NMP in a mass ratio of 80:5:15 for slurrying, and the solid content is controlled at 50%. After the slurrying is completed, the slurry is evenly coated on the aluminum foil current collector with the help of an automatic coating machine, and transferred to a vacuum drying oven at 120°C for drying for 12 hours. Take out the material and cool it naturally to room temperature, cut it into pieces using a manual battery slicer, collect the cut positive electrode sheets, put them into a ziplock bag after weighing, and place them in a glove box filled with inert gas for standby use. With a metal sodium sheet as the negative electrode and a GF / A type glass fiber diaphragm as the diaphragm, an electrolyte is added to assemble a CR2032 button battery, and the electrochemical performance test is carried out after standing. The electrochemical performances were tested using a CT-2001A battery testing system (1C = 129 mA / g), where the voltage range for constant current charge and discharge testing was 1.5 to 4.0 V.

[0101] The results are shown in Table 1.

[0102] Table 1 Battery performance of heteroelement-doped carbon-coated polyanion cathode materials

[0103]

[0104]

[0105] As shown in Table 1, the heteroelement-doped carbon-coated polyanion cathode material of the present invention has a 3+x M 2+x (PO4) 1+ x The surface of P2O7 material, PN / C, phosphorus and nitrogen co-doped carbon coating, is a sheet structure with high sp 2 Hybrid carbon structure, excellent conductivity, and phosphorus and nitrogen co-doped carbon coating layer cooperate with each other, reasonably activate the hybrid phase, improve capacity and cycle performance, high conductivity PN / C, phosphorus and nitrogen co-doped carbon coating layer, and core Na 3+x M 2+x (PO4) 1+x The synergistic effect of P2O7 improves the overall performance of the material, including capacity and cycle performance. Moreover, the doping of phosphorus is different from that of other elements in the coating layer. 3+x M 2+x (PO4) 1+x P2O7 material is mainly composed of phosphate pyrophosphate, and phosphorus is doped as a coating layer. 3+x M 2+x(PO4) 1+x The phase composition of P2O7 does not cause adverse interference, and the high conductivity PN / C is achieved. The carbon coating layer co-doped with phosphorus and nitrogen is 3+x M 2+x (PO4) 1+x P2O7 produces synergy and overcomes the adverse effects of phosphorus doping on the phase composition of the core material.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A heteroelement-doped carbon-coated polyanion positive electrode material, characterized in that: The general structural formula of the polyanion positive electrode material is Na 3+x M 2+x (PO4) 1+x P2O7@PN / C, wherein 0≤x≤2, M is one or more of Ni, Fe, Co, and Mn, and the polyanion cathode material is a core-shell structure, Na 3+x M 2+x (PO4) 1+x P2O7 is the core of the core-shell structure of the polyanion positive electrode material, @PN / C represents a coating layer formed on the surface of the core material, and PN / C is a carbon coating layer co-doped with phosphorus and nitrogen.

2. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 1, characterized in that: The preparation method of PN / C comprises the following steps: uniformly dispersing an organic carbon source, an organic phosphorus source and an organic nitrogen source, heating the mixture to 600-1000° C. in an inert gas atmosphere, and then sintering the mixture at a constant temperature for 5-20 hours to obtain a PN / C carbon material.

3. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 1, characterized in that: The mass of the PN / C coating layer accounts for 0.1% to 5.0% of the mass of the polyanion positive electrode material.

4. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 3, characterized in that: The mass of the PN / C coating layer accounts for 0.5% to 3.0% of the mass of the polyanion positive electrode material.

5. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 2, characterized in that: In the process of preparing PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic phosphorus source, organic nitrogen source and organic carbon source is a:b:100, wherein 1.0≤a≤10; 20≤b≤50.

6. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 5, characterized in that: In the process of preparing PN / C carbon material, the weight ratio of phosphorus element, nitrogen element and carbon element in the organic phosphorus source, organic nitrogen source and organic carbon source used is a:b:100, wherein 3≤a≤8; 30≤b≤45; the organic carbon source is one or more of glucose, chitosan, sucrose, starch, citric acid, sodium citrate, lauric acid and sodium laurate; the organic phosphorus source is one of triphenylphosphine and phytic acid; the organic nitrogen source is one or more of melamine, urea and chitosan.

7. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 2, characterized in that: The preparation method of the polyanion positive electrode material comprises the steps of: sintering the PN / C carbon material and Na 3+x M 2+x (PO4) 1+x The precursor materials of P2O7 are dispersed and mixed, and then heated to 420-600°C in an inert gas atmosphere and sintered at a constant temperature for 5-20 hours to obtain Na 3+x M 2+x (PO4) 1+x P2O7@PN / C.

8. The heteroelement-doped carbon-coated polyanion positive electrode material according to claim 7, characterized in that: Na 3+x M 2+x (PO4) 1+x The precursor of P2O7 includes a sodium source, an M source, and a phosphorus source. The sodium source is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrate, and sodium citrate; the M source is one or more of phosphates, nitrates, sulfates, oxalates, acetates, and oxides corresponding to one or more metal elements of Ni, Fe, Co, and Mn; and the phosphorus source is one or more of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, sodium pyrophosphate, iron phosphate, and iron pyrophosphate.

9. The method for preparing the heteroelement-doped carbon-coated polyanion positive electrode material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: (1) grinding and mixing an organic carbon source, an organic nitrogen source, and an organic phosphorus source according to a weight ratio, and then sintering in one step or two steps under an inert gas atmosphere to obtain a PN / C carbon material; (2) according to the preset x value, the PN / C carbon material, the sodium source, the M source and the dispersant are dispersed or dissolved in a solvent according to a stoichiometric ratio and ground to obtain a mixed slurry H2, and after removing the solvent and drying H2, a precursor material to be sintered H3 in which each element is evenly dispersed is obtained; (3) The obtained H3 is subjected to a one-step or two-step sintering treatment in an inert atmosphere to obtain a polyanion positive electrode material doped with heteroelement carbon.

10. The method for preparing the heteroelement-doped carbon-coated polyanion positive electrode material according to claim 9, characterized in that: In step (1), the grinding process is a ball milling process, wherein the rotation speed of the ball milling process is 400-800 rpm, the ball-to-material ratio is 2-20:1, the diameter of the zirconia ball is 0.1-0.5 mm, and the ball milling time is 2-5 h; In step (2), the grinding process includes a ball milling process and a sand milling process in sequence, wherein the ball milling speed is 400-800 rpm; the ball-to-material ratio is 2-20:1, and the diameter of the zirconia ball is 0.1-0.5 mm; the solid content of the sand milling is 15%-40%, and the sand milling speed is 1000-2400 rpm; the particle size of the solid in the slurry after sand milling is D50≤6μm, Dmax≤30μm; In step (2), the dispersant is one or more of PVP, PVA, NPEOs, PEG, APG, and PAA; In step (2), the solvent is one of water, methanol, ethanol, acetone, ethylene glycol and n-butanol; In step (2), the drying method is spray drying, freeze drying, high temperature drying or vacuum drying, and the drying temperature is not higher than 280° C.; In step (1), in the one-step sintering or two-step sintering, the procedure of the one-step sintering is to heat the material to 600-1000°C at a heating rate of 1-5°C / min in an inert protective atmosphere, and sinter at a constant temperature for 5-20 hours; then cool it to room temperature at a cooling rate of 2-10°C / min; the procedure of the two-step sintering is to heat the material to a pre-sintering temperature of 400-550°C at a heating rate of 1-5°C / min in an inert protective atmosphere for 2-4 hours; then heat the material to 600-1000°C at a heating rate of 3-6°C / min for 4-10 hours; then cool it to room temperature at a cooling rate of 2-10°C / min; In step (3), in the one-step sintering or two-step sintering, the procedure of the one-step sintering is, in an inert protective atmosphere, heating to 420-600°C at a heating rate of 1-5°C / min, and sintering at a constant temperature for 5-20 hours; then cooling to room temperature at a cooling rate of 2-10°C / min; the procedure of the two-step sintering is, in an inert protective atmosphere, heating to a pre-sintering temperature of 250-420°C at a heating rate of 1-5°C / min for 2-4 hours; then heating to 520-600°C at a heating rate of 3-6°C / min for 4-10 hours; then cooling to room temperature at a cooling rate of 2-10°C / min.

Citation Information

Patent Citations

  • Transitional metal phosphide-carbon composite material as well as preparation method and application thereof

    CN108511714A

  • Transition metal doped titanium manganese sodium phosphate / carbon composite positive electrode material, preparation thereof and application in sodium ion battery

    CN110611080A

  • Preparation and application method of high-capacity sodium-ion battery positive electrode material

    CN117525315A

  • Nitrogen and sulfur co-doped modified carbon coated ferric sodium pyrophosphate composite material as well as preparation method and application thereof

    CN117727893A

  • Nitrogen-doped carbon-coated composite Na4Fe3 (PO4) 2P2O7 sodium ion battery positive electrode material and preparation method thereof

    CN118352495A